Steady Aircraft Flight and Performance. - McClamroch, N. H. (Princeton University Press, 2011)
This undergraduate textbook offers a unique introduction to steady flight and performance for fixed-wing aircraft from a twenty-first-century flight systems perspective. Emphasizing the interplay between mathematics and engineering, it fully explains the fundamentals of aircraft flight and develops the basic algebraic equations needed to obtain the conditions for gliding flight, level flight, climbing and descending flight, and turning flight. It covers every aspect of flight performance, including maximum and minimum air speed, maximum climb rate, minimum turn radius, flight ceiling, maximum.